Homeland on Parade: The Azorean Diaspora, Performance, and the Politics of Celebration - Cordeiro, Graça Índias; Formato, G. (Homeland on Parade: The Azorean Diaspora, Performance, and the Politics of Celebration, 2025)
In the early 1930s, a massive celebration brought up to 100,000 people to the streets of Cambridge and Somerville to mark the 500th anniversary of the discovery of the Azores. Organized by the Portuguese American Civic League and widely covered by the press, the event highlighted the role of public ritual in asserting ethnic identity and transnational belonging. Despite a long-standing presence in the region, Azorean cultural visibility has been increasingly marginalized, especially amidst recent gentrification in Greater Boston. This presentation revisits that historic moment to explore how Azorean-American communities have negotiated their place across local and diasporic contexts, and how Estado Novo cultural diplomacy (1933–1974) contributed to reshaping or erasing their distinct identity. The talk draws on the research project Exporting Portugal: Estado Novo Cultural Diplomacy and Rebranding Strategies in the United States (1933–1974), which is hosted by the Institute of Social Sciences (ICS), University of Lisbon, and funded by FCT. It is coordinated by Annarita Gori.